Development of a repeat-exposure penile SHIV infection model in macaques to evaluate biomedical preventions against HIV - Garber, David A. (PLoS One, 2018)
Penile acquisition of HIV infection contributes substantially to the global epidemic. Our goal was to establish a preclinical macaque model of penile HIV infection for evaluating the efficacy of new HIV prevention modalities. Rhesus macaques were challenged once or twice weekly with consistent doses of SHIV(sf)162P3 (a chimeric simian-human immunodeficiency virus containing HIV env) ranging from 4–600 TCID(50) (50% tissue culture infective dose), via two penile routes, until systemic SHIV infection was confirmed. One route exposed the inner foreskin, glans and urethral os to virus following deposition into the prepuce (foreskin) pouch. The second route introduced the virus non-traumatically into the distal urethra only. Single-route challenges resulted in dose-dependent rates of SHIV acquisition informing selection of optimal SHIV dosing. Concurrent SHIV challenges via the prepuce pouch (200 TCID(50)) and urethra (16 TCID(50)) resulted in infection of 100% (10/10) animals following a median of 2.5 virus exposures (range, 1–12). We describe the first rhesus macaque repeat-exposure SHIV challenge model of penile HIV acquisition. Utilization of the model should further our understanding of penile HIV infection and facilitate the development of new HIV prevention strategies for men.